The importance of the marine ornamental reef fish trade in the wider Caribbean - Bruckner, A. W. (2005)
The marine ornamental fish trade began in the 1930s in Sri Lanka, spread to Hawaii and the Philippines in the 1950s, and expanded to a multi-million dollar industry in the 1970s with fisheries established throughout the tropical Pacific, Indian and Atlantic Oceans. Currently, 45 countries supply global markets an estimated 14-30 million fish annually, with an import value of US$28-44 million. The largest suppliers are Indonesia and the Philippines, followed by Brazil, Maldives, Vietnam, Sri Lanka and Hawaii. In the tropical Western Atlantic, 16 countries have export fisheries, including the U.S. (Florida and Puerto Rico). The U.S. is the world’s largest buyer, followed by the European Union and Japan. The global trade consists of over 1400 species of reef fishes, of which only about 25 are captive bred on a commercial scale. Damselfish, anemonefish, and angelfish constitute over 50% of the global volume; butterflyfish, wrasses, blennies, gobies, triggerfish, filefish, hawkfishes, groupers and basselets account for 31% of the trade, and the remaining 16% is represented by 33 families. The most important fishes from the Caribbean are angelfish (six species), seahorses (two species), royal gramma, jawfish, queen triggerfish, redlip blenny, puddingwife, bluehead wrasse, and blue chromis. The Caribbean currently supplies a small percentage of the global trade in marine ornamental species, but ornamental fisheries in this region represent important emerging industries. It is critical that effective ornamental fishery management plans and regulations are developed and enforced, and fishery-dependent and fishery-independent data are collected and utilized in decision making processes to ensure sustainable ornamental fisheries throughout the region.